Detection of antibodies to Chlamydophila pneumoniae by immunoblotting in patients with cardiovascular diseases - Kovácová, E; Mongiellová, M; Tomka, J; Slysko, R; Kazár, J (Epidemiologie, mikrobiologie, imunologie, 2009)
Chlamydophila pneumoniae, one of the most prevalent human pathogens worldwide, is not only a significant cause of pneumonia, but may also be associated with cardiovascular diseases (CVD) as suggested by multiple studies. A total of 228 sera from CVD patients with hypertension, ischemic heart disease or previous reconstructive vascular surgery were screened for the presence of anti-C. pneumoniae IgG and IgA antibodies by ELISA. Out of 150 positive serum samples, 80 with similar IgG and IgA levels were investigated by immunoblot (IB). IgG antibodies were directed predominantly against the 35 kDa and 39 kDa proteins as well as 50-54 and 56-60 kDa proteins of C. pneumoniae. IgA antibodies reacted most frequently with the 50-54 and 56-60 kDa proteins.
Keywords: protilátky bakteriální; imunoblotting; Immunoblotting; Chlamydophila pneumoniae; kardiovaskulární nemoci; Cardiovascular Diseases; lidé; Immunoglobulins; lidé středního věku; Humans; Antibodies, Bacterial; imunoglobuliny; Middle Aged